The Effect of CORE Learning Model towards Students’ Mathematical Reflective Thinking Skills: A Meta Analysis Study - Syofitami, Raisa Adira; Noer, Sri Hatuti (FKIP Universitas Lampung, 2021)
This study aims to re-analyze the CORE type of cooperative learning model related to students' mathematical reflective thinking abilities. The CORE model consists of four stages, namely Connecting, Organizing, Reflecting and Extending. In this study, researchers used the meta-analysis method. First, the researcher formulates the research problem, then proceeds to explore existing and relevant research for analysis. Data collection techniques using non-test, namely by browsing electronic journals through Google Scholar and studying documentation in the library. From the search results obtained 6 articles from journals. Based on the results of the analysis, it turns out that the CORE type of learning model is able to have an effect on students' reflective thinking skills. Keywords: reflective thinking, cooperative learning, CORE learning model. DOI: http://dx.doi.org/10.23960/jpmipa/v22i1.pp90-97